2013
DOI: 10.1063/1.4794958
|View full text |Cite
|
Sign up to set email alerts
|

Roles of trichomes with silica particles on the surface of leaves in Aphananthe aspera

Abstract: There exist many trichomes with silica particles on the surface of leaves in Aphananthe aspera (Muku tree). The size of the trichomes is on the order of some tens to hundreds of micrometers. Investigating the electric-field local densities of the states and distributions of electromagnetic wave propagation, we theoretically revealed that while trichomes play a role as waveguides for the far-infrared, silica particles help incident far-infrared light efficiently propagate inside the trichomes and leaves. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…According to Takeda et al . (), silicified trichomes could efficiently help plants to absorb visible light. Waterkeyn et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Takeda et al . (), silicified trichomes could efficiently help plants to absorb visible light. Waterkeyn et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies showed that the silicified bulliform cells are favored when transpiration is high (Takeoka et al, 1984) or simply when the Si content in soils is high (Fernandez Honaine & Osterrieth, 2012). According to Takeda et al (2013), silicified trichomes could efficiently help plants to absorb visible light. Waterkeyn et al (1982) suggested that silicified trichomes are areas of intense transpiration and may thus contribute to cooling plants; however, this remains speculative (Hodson et al, 1985;Kaufman et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The increased silicification in acute bulbosus in relation to Si availability is in agreement to Meunier et al (2017), who also did not find a relation with water stress and consider that these cells may act as a reservoir of excess Si. Instead, Takeda et al (2013) associated the presence of silica in trichomes with an improvement of photosynthesis, due to a higher absorption of far-infrared light. Lastly, a higher accumulation of silica resulting in multicellular deposits (silica skeletons) may favor the erectness of leaves, also promoting photosynthesis (De Tombeur et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Trichomes with silica particles were found on the leaves of Aphananthe aspera , which appeared to help incident far-infrared light to propagate efficiently inside the trichomes and leaves. It is believed that this, in turn, helped to heat the plant 12 .…”
Section: Introductionmentioning
confidence: 99%